The impact of results based management on service delivery, Case Of Ministry of Local Government, Public Works and National Housing - Maposa, Lilian Sibusisiwe (2017)
The main aim of this study was to investigate the impact of results based management on service delivery. Gweru Public Works was used by the researcher as the case study. Literature was reviewed in order to establish the existing gap on impact of results based management and service delivery. To capture reality as it was seen and experienced by the respondents the researcher used both qualitative and quantitative of data analysis. During data collection questionnaires and interviews were used and the data collected was analysed and presented in tables, pie charts and graphs. The findings revealed that though Public Works uses results based management as a tool to enhance service delivery, both employees and the head of departments do not understand it because of ignorance and lack of training and therefore hindering the success stories of RBM in delivering services. The study also revealed that lack of resources to carry out work and lack of incentives also affects results based management. Recommendations to train and incentivise employees were suggested to the organisation.